A multicenter observational study of the real‐world use of docetaxel for metastatic castration‐resistant prostate cancer in China. Issue 3 (15th March 2019) - He, Dalin; Sun, Zhongquan; Guo, Jianming; Zhang, Zhigen; Shan, Yuxi; Ma, Lulin; Li, Hanzhong; Jin, Jie; Huang, Yiran; Xiao, Jiaquan; Wei, Qiang; Ye, Dingwei
Abstract: Aim: To investigate the use of docetaxel for the treatment of metastatic castration‐resistant prostate cancer (mCRPC) in real‐world clinical practice in China. Methods: This single‐arm, prospective, observational study was conducted at 32 study centers in China and included male patients aged ≥18 years with histologically confirmed prostate cancer who received ≥1 dose of docetaxel following failure of hormonal therapy (disease progression with serum testosterone <50 ng/dL). The primary aim was to investigate patterns of docetaxel treatment. Results: Overall 403 patients were included between August 2011 and June 2016; patients initiated docetaxel after failure of first‐ (42.2% [170]), second‐ (31.0% [125]) and ≥third‐line (12.7% [51]) hormonal therapy, estramustine (11.4% [46]) or other (2.7% [11]). The planned cycles of docetaxel therapy were completed by 30.8% of patients, and the mean (SD) number of cycles received was 4.4 (2.86). Median overall survival (mOS) was 22.4 (95% CI, 20.4–25.8) months and the prostate‐specific antigen (PSA) response rate in patients with available data was 70.9% (168/237), with no differences in mOS and PSA response rates between treatment settings. Subgroup analysis revealed higher mOS in patients without visceral metastasis versus those with such metastases (22.9 vs. 17.4 months; P = 0.022). No new safety signals were observed and the most common adverse events associated with docetaxel were granulocytopenia (5%) and leukopenia (4.5%). Conclusion: Data from this study showed that around three‐quarters of Chinese patients with mCRPC treated with docetaxel initiated treatment following first‐ or second‐line hormonal therapy and no new safety signals were observed.